A case of recurrent intussusception in young adult female: Peutz Jegher syndrome - Gupta, Brajesh B.; Jadhav, Ganesh D.; Bhingare , Pravin; Dakhore, Sanjay; Kodape, Amit; Gupta, Shweta; Jain, Manali; Deshmukh , Karishma (International Surgery Journal, 2023)
Peutz Jegher syndrome (PJS) is an autosomal dominant inherited polyposis syndrome, in which multiple characteristic polyps occur in the gastro-intestinal tract associated with mucocutaneous pigmentation especially of vermillion border of the lips. Small bowel obstruction is presenting complaint in half of the cases-intussusception due to polyp being lead point is the high risk for obstruction. A 21 year old female patient with presented to emergency department with complaining of intermittent episodes of abdominal pain and multiple episodes of billious vomiting since 7 days. Patient had history of exploratory laparotomy 10 years back for similar complaints. On examination, melanocytic pigmentation present over vermillion border and palmar aspect. Enhanced computed tomography reveals telescoping of the distal jejunum to proximal ileal loops s/o jejuno-ileal intussusception with ileo-ileal intussusception were noted. On surgical decision, patient again underwent exploratory laparotomy which revealed intussusception with non-viable small bowel segment were found, Small bowel resection was performed and jejuno-ileal anastomosis was done. Patient follow up was maintained to go with colonoscopic evaluation. In conclusion, recurrent intussusception is a rare cause of acute abdomen in adults. A high index of suspicion and appropriate investigations are helpful in prompt diagnosis. Thorough evaluation intra operative and then regular periodic follow up is required in such cases for early detection of disease before complication occurs.